Male infertility and erectile dysfunction in patients with vasculitis - Keskin, Hakan; Altan, Mesut (Acta Medica, 2025)
Erectile dysfunction and male infertility are increasingly recognized complications in patients with vasculitis, arising from both disease-related mechanisms and treatment effects. Chronic inflammation, vascular involvement, and hormonal dysregulation may impair erectile function and reproductive capacity. Furthermore, commonly used medications such as steroids and immunosuppressants can negatively impact semen quality and may exert teratogenic effects. Studies have also demonstrated high rates of hypogonadism and sexual dysfunction in specific vasculitis subtypes, including granulomatosis with polyangiitis and Behçet’s disease. Given the limited evidence base, multidisciplinary evaluation and proactive counseling regarding sexual health, fertility intentions, and treatment risks are essential.